Australia's changing export pattern - P. E. Stonham (Intereconomics, 1967)
Australia is frequently considered a farming country on the periphery of the world economy, whose exports are traditionally restricted to wheat, wool and dairy produce. However, this conception does not correspond anymore to the present shape of the Australian economy. After World War Il structural changes linked up the country with the world economy on a broader base, and Industrial products are becoming more and more Important to Australian exports. The following article deals with the determining factors of Australia's export oriented industrialisation and the future prospects for its progress from a farming country to an industrial nation.
Keywords: 330; Foreign Trade